Local Wisdom-Based Stories in Conserving Water Resources - Dewi, Dian Novita; Kusumawardani, Irene Nany; Lintangsari, Alies Poetri (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2020)
Along with the rapid development of technology, local wisdom tends to run into marginalization so that it is completely lost (Choesin, 2002 cited in Rasna & Tantra, 2017). The local wisdom should be able to become a milestone in the community in order to preserve the cultural heritage and the natural resources. Meanwhile, a transformation towards sustainability is urgently needed for our planet, and every other living thing on it including the resources it provides. Therefore, this study aims at exploring the local wisdoms that still exist and develops at several springs in Singosari Malang. Locations were chosen based on the profile of the springs which still have good management based on the local wisdom that are passed on through generations. The springs include Sumber Biru and Sumber Nagan in Gunungrejo village, Singosari District Malang. The research approach used is ethnographic research. Interviews, focused discussions, and documentation were the techniques used to collect the data. The result is descriptively presented in a form of a history of the springs which is retold in the form of short story.Â DOI: https://doi.org/10.26905/lw.v12i1.3646